APPLICATION OF TOPOLOGICAL TECHNIQUE METHODS IN POWER FLOW COMPUTATION OF RADIAL DISTRIBUTION NETWORKS WITHOUT ITERATON AND WITH ITERATED - Cekmas Cekdin, Muhammad Saleh Al Amin, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In computing power flow in a radial distribution network system, it is rather difficult to do. Because it is not easy to reach a convergence point. In another case, the loop or ring distribution network system is easy to reach a convergence point. By using topological engineering methods, power flow computation in a radial distribution network system can be done with the help of computer software. The computation that will be carried out is the amount of voltage, voltage drop, current and power on the conductor and the losses that occur in the network. The calculation is done in two ways, namely iteratively and without iteration. From the two calculations, it can be shown that the calculation without iteration is good enough to be used in calculating the power flow of the radial distribution network.